Antecedents of Freelance Tutor Loyalty at IBSI Education: A Job Satisfaction Mediation Study - Irma Arista (Universitas Hayam Wuruk Perbanas, 2025)
With job satisfaction serving as an intermediary variable, the purpose of this study was to investigate how job engagement, pay, and perceived organizational support affect the loyalty of independent tutors employed by IBSI Education. This study used a quantitative approach, collecting data from 208 participants and processing it using the PLS SEM technique with the aid of SmartPLS 4.0 software. The findings show that loyalty is significantly positively impacted by work engagement, pay, and perceived organizational support. The mediation test's findings demonstrated that job satisfaction significantly mediated the relationships between perceived organizational support and loyalty as well as between work engagement and loyalty. On the other hand, job satisfaction did not play a substantial mediating role in the link between loyalty and compensation. These results imply that while perceived organizational support and work engagement necessitate job satisfaction to optimize retention, fair compensation immediately fosters loyalty for independent tutors regardless of satisfaction levels. In order to lower tutor turnover, this study advises IBSI Education administration to maintain a competitive honorarium system and bolster operational support.